Urban Sustainability Assessment Tool for Hillside Planning, Design, and Development - Kaur H.; Garg P. (My University, 2025)
Hillside planning, design, and development require an intensive understanding of human habitats, man-environment interaction, hill environment sensitivities, spatial planning, and design issues to ensure contextually appropriate development. Although numerous tools, techniques, and frameworks have been developed and implemented to assess urban sustainability, these have not been applied to environmentally sensitive hilly areas, nor have their appropriateness been determined. Therefore, this paper aims to develop a new urban sustainability assessment tool (USAT) named the "Sustainable Urban Development of Environmentally Sensitive Hilly Areas Suitability IndeX (SUDESHA-SIX)"to evaluate the sustainability of hillside settlements using an analytical hierarchy process. The methodology combines descriptive and deductive analytical techniques and geographic information systems-based statistical methods. SUDESHA-SIX was first developed some years back and was applied to the New Tehri Township as it received the National Award for Excellence in planning and design in hills in the year 2000 by the then Prime Minister of India. The results showed that out of the six broad factors, "site suitability"was ranked as the most critical factor of environmentally sensitive hilly areas, followed by "built environment,""environment and ecology,""climate and energy,""transportation and connectivity,"and "visual resources."When applied to existing projects, the developed tool provided a more objective and detailed information on the urban sustainability of hilly areas, which could help architects, planners, designers, and decision-makers develop strategies to improve the overall urban sustainability of hilly regions. © 2023 American Society of Civil Engineers.